Autonomous microgrid based parallel inverters using droop controller for improved power sharing - Siddaraj Siddaraj; Udaykumar R. Yaragatti; Nagendrappa H.; Vikash Kumar Jhunjhunwala (Bulletin of Electrical Engineering and Informatics, 2020)
The existing microgrid has become a challenge to the sustainable energy source to provide a better quality of power to the consumer. To build a reliable and efficient microgrid, designing a droop controller for the microgrid is of utmost importance. In this paper, multiple voltage source inverters connected in parallel using an active power-frequency/reactive power-voltage droop scheme. The proposed method connected to two distributed generators local controllers, where each unit consists of a droop controller with an inner voltage-current controller and a virtual droop controller. By adding this controller to the microgrid reliability and load adaptability of an islanded system can be improved. This concept applied without any real-time communication to the microgrid. Thus, simulated using MATLAB/Simulink, the obtained results prove the effectiveness of the autonomous operation's microgrid model.